Unleashing Potential: How Talent and Career Management Drive Employee Performance through Motivation (Case Study on Employees of PT. Infomedia Nusantara, Jakarta) - Dimas Ryanto; Nuraeni Nuraeni; Maswanto Maswanto (Dinasti International Journal of Education Management And Social Science, 2025)
This study focuses on the impact of Talent Management and Career Management on employee performance through motivation, with a case study at PT Infomedia Nusantara Jakarta. The research is motivated by the need for high-quality human resources and efforts to retain them through development and career opportunities, expected to enhance motivation and improve performance. This quantitative study involves employees of PT Infomedia Nusantara Jakarta, with a sample of 109 respondents selected using simple random sampling based on the Slovin formula. Data were collected through questionnaires and analyzed using t-tests, F-tests, structural analysis, and path analysis methods. The results indicate that Talent Management has no significant effect on motivation and performance, whereas Career Management has a significant positive impact on motivation but no direct effect on performance. Motivation itself significantly and positively influences employee performance. Overall, the Talent Management program plays a minimal role in enhancing motivation and performance, while the Career Management program indirectly has a strong role in improving performance through motivation. If these programs are implemented effectively, both employee motivation and performance are expected to improve